Isolation of chemical constituents with anti-inflammatory activity from Reineckia carnea herbs. Issue 4 (2nd April 2020) - Xu, Xu; Tan, Ting; Zhang, Jing; Li, Zhi-Feng; Yang, Shi-Lin; Wen, Quan; Feng, Yu-Lin
Abstract: Three new saponins (1–3 ), a new natural product (4 ) and six other known compounds (5–10 ) were isolated from the whole Reineckia carnea plant. Their structures were established by comparison of their NMR spectra and MS data with literature data. In addition, all the isolated compounds were evaluated in vitro for anti-inflammatory activities against LPS-stimulated nitric oxide (NO) production in RAW 264.7 macrophages. Compounds 1–4 exhibited anti-inflammatory activities with IC50 values of 37.5 µM, 31.4 µM, 34.6 µM, and 56.1 µM, respectively. Furthermore, compounds 5–10 showed anti-inflammatory activities with IC50 values ranging from 20.3 to 42.9 µM. Graphical Abstract: